Functional analysis of the peroxisomal and mitochondrial proteins MFF and FIS1 in HCMV evasion of the cellular antiviral response - Gouveia, Ana Maria da Silva (2023)
Peroxisomes are single membrane bound organelles involved in crucial cellular metabolic functions. They were noticed for the first time in the 1960s and, along the years, their importance for the cellular homeostasis has been increasingly highlighted. Peroxisomes and mitochondria cooperate in several cellular metabolic processes and more recently were found to have a complementary role in the antiviral innate immune response. These two organelles also share many proteins including the fission machinery key proteins MFF, FIS1 and DLP1 and the antiviral signaling protein MAVS. As the proper function of these organelles strongly depends on the capacity to adequate their shape and cellular localization in accordance with the cellular needs, and thus on the correct regulation of membrane fission events, in this work we evaluated the role of the peroxisomal and mitochondrial fission machinery, specially the key DLP1 adaptors MFF and FIS1 in the antiviral immune response against one of the most spread viruses in the community: the human cytomegalovirus (HCMV). In line with this, we started this work by characterizing the peroxisomal fission machinery and by distinguishing different roles of key components shared with mitochondria (MFF e FIS1). The role of these proteins in the peroxisomal antiviral signaling against HCMV was afterwards analyzed in detail. Our results strongly indicate that MFF plays a crucial role at the regulation of peroxisomal fission whereas FIS1 significantly impacts mitochondrial fission events. In addition, we found that MFF interacts with the HCMV viral protein vMIA and that it is essential to vMIA´s function. MFF seems to, thus, play a crucial role in HCMV´s infection. Altogether, these results empathize the importance of peroxisomal fission machinery for the RLR-mediated antiviral defense and may lead to the discovery of novel peroxisome-dependent mechanisms, which can ultimately be used as targets for antiviral therapy.